Wahid Hasyim’s Thoughts (Religious-Rational) About Education and Its Relevance to The Contemporary Islamic Education - Muhammad Syahdan Majid; Ahmad Saufi Al Hadisi; Abdul Rohman; Hasan Asy`ari Yusuf (Nazhruna: Jurnal Pendidikan Islam, 2022)
Abstract In the view of many education experts, Islamic education in Indonesia is still lagging compared to general education in several aspects. One of the reasons for this is that Islamic education's orientation is only on religion. There are three of Wahid Hasyim's thoughts to advance Islamic education in Indonesia: education, curriculum, and learning methods. This renewal became a spur in advancing Islamic education in Indonesia at that time, and this is what made the writer interested in elevating Wahid Hasyim's thoughts on Contemporary Islamic education. The research method used in this study is the Library Research method, namely activities related to collecting library information and reading and processing research. This study aims to find the relevance of Abdul Wahid Hasyim's (Rational-Religious) thoughts on Contemporary Islamic education. As a result, the authors found the relevance of Wahid Hasyim's thoughts through descriptive analysis, namely the latest learning methods and modern educational curricula.